Pivotal role of bZIPs in amylose biosynthesis by genome survey and transcriptome analysis in wheat (Triticum aestivum L.) mutants. Issue 1 (December 2018) - Kumar, Pankaj; Mishra, Ankita; Sharma, Himanshu; Sharma, Dixit; Rahim, Mohammed; Sharma, Monica; Parveen, Afsana; Jain, Prateek; Verma, Shailender; Rishi, Vikas; Roy, Joy
Abstract Starch makes up 70% of the wheat grain, and is an important source of calories for humans, however, the overconsumption of wheat starch may contribute to nutrition-associated health problems. The challenge is to develop resistant starch including high amylose wheat varieties with health benefits. Adapting advance genomic approaches in EMS-induced mutant lines differing in amylose content, basic leucine zipper (bZIP) regulatory factors that may play role in controlling amylose biosynthesis were identified in wheat. bZIP transcription factors are key regulators of starch biosynthesis genes in rice and maize, but their role in regulating these genes in wheat is poorly understood. A genome-wide survey identified 370 wheat bZIPs, clustered in 11 groups, showing variations in amino acids composition and predicted physicochemical properties. Three approaches namely, whole transcriptome sequencing, qRT-PCR, and correlation analysis in contrasting high and low amylose mutants and their parent line identified 24 candidate bZIP (positive and negative regulators), suggesting bZIPs role in high amylose biosynthesis. bZIPs positive role in high amylose biosynthesis is not known.In silico interactome studies of candidate wheat bZIP homologs inArabidopsis and rice identified their putative functional role. The identified bZIPs are involved in stress-related pathways, flower and seed development, and starch biosynthesis. An in-depth analysis of molecular mechanism of novel candidate bZIPs may help in raising and improving high amylose wheat varieties.